Insufficient Angiogenesis: Cause of Abnormally Thin Endometrium in Subfertile Patients? - Alfer, Joachim; Happel, Lars; Dittrich, Ralf; Beckmann, Matthias W.; Hartmann, Arndt; Gaumann, Andreas; Buck, Volker U.; Classen-Linke, Irmgard (Geburtshilfe und Frauenheilkunde, 2017)
Introduction This study investigated subfertile patients with abnormally thin endometrium after infertility treatment. As they had adequate serum concentrations of hormones, an endometrial factor for subfertility was suspected.Methods To elucidate the cause of subfertility, endometrial biopsies were taken in each patient in the late proliferative and mid-secretory phases of one menstrual cycle. Endometrial biopsies from women with normal menstrual cycles and confirmed fertility who were undergoing hysterectomy for benign uterine disease were used as positive controls. The tissue samples were investigated for steroid hormone receptor expression and for the proliferation marker Ki-67. Immunohistochemistry was performed with antibodies against the marker molecules for endometrial receptivity – β3 integrin, VEGF, LIF, and CD56 (large granular lymphocytes, LGLs).Results The steroid hormone receptors for estrogen (E2) and progesterone (P) were expressed normally (at the first biopsy) and were down-regulated (at the second biopsy) within the cycle. Strikingly, all of the marker molecules investigated showed negative or weak and inadequate expression in the mid-secretory phase. Numbers of LGLs remained as low as in the proliferative phase. In contrast, fertile patients were found to express these marker molecules distinctly in the mid-secretory phase.Conclusions It may be hypothesized that a severe deficiency of these angiogenesis-related marker molecules leads to defective development of the endometrium, which remains thin. Deficient angiogenetic development may thus provide an explanation for the endometrial factor that causes infertility. Further investigations will need to focus on identifying the regulating factors that act between steroid receptor activation and the expression of these marker molecules.
Keywords: thin endometrium; IVF; LIF; VEGF; β3 integrin; angiogenesis